Experiencing Cybersecurity One Game at a Time: A Systematic Review of Cybersecurity Digital Games - Coenraad, Merijke; Pellicone, Anthony; Ketelhut, Diane Jass; Cukier, Michel; Plane, Jan; Weintrop, David (Simulation & gaming, 2020)
Background. Cybersecurity is of increasing importance in our interconnected world, yet the field has a growing workforce deficit and an underrepresentation of women and people of color. In an effort to address these issues, many digital games have been created to teach individuals about cybersecurity and keeping themselves, their data, and their networks safe. Intervention. We present the results of a systematic review of digital games related to cybersecurity as a means to understand how players are being introduced to cybersecurity in game-based contexts. Methods. Using a systematic search, we identified 181 games related to cybersecurity (either through content or aesthetics) by searching the Apple App Store, the Google Play Store, Steam, and the web broadly. Each game was played for up to an hour and characteristics such as the game story, game elements, and presentation of cybersecurity were gathered. Results. We found diverse conceptualizations of cybersecurity and of cybersecurity professionals. Further, the nature of games and the framing of cybersecurity varied by the platform and device on which the game was available (computer, mobile, or web). Web games were most likely to present cybersecurity as cyber safety and were more likely to be a gamified quiz or worksheet. Computer and mobile games tended to present cybersecurity through game aesthetics or deep content engagement. The games mirrored the underrepresentation of women and minoritized individuals in the field. Discussion. With the variety of digital cybersecurity games and the differences in games based on the platform on which the game is available, it is important game developers move beyond presenting cybersecurity through gamification and focusing on cyber safety. The current scope of cybersecurity games leaves room for the development of games focused on deeper content engagement with cybersecurity topics in an environment conducive to the broadening participation goals of the cybersecurity field.